Environmental fragmentation in the State Park Morro do Diabo in Teorodo Sampaio, SP, Brazil - de Moura, Marta Aparecida; Arana, Alba Regina Azevedo (Sustainability in Debate, 2018)
Anthropogenic action can cause pollution, depredation and deforestation, leading to interference with biodiversity, ecological balance, and environmental impact and damage. We chose to study the Morro do Diabo State Park (MDSP) in Teodoro Sampaio-SP. This article aims to make an historical analysis of the public policies that determined the formation of the territory in the municipality and the environmental impacts caused since the legalization of the MDSP from 1941 to 2006. We used a qualitative-quantitative approach, for the construction of the linear history of environmental impacts in the Park. We verified that there was a gradual territorial loss of 9.31% corresponding to 3,311.35 hectares during the 65-year-period analyzed and that the main environmental damage was the implantation and construction of the Hydroelectric Plant of Rosana, which caused the deforestation of about 5.53% of the total area.